Effect of Substitusion of Tubifex sp. With Artificial Feed On Growth, Survival Rate and Feed Eficiency Of Hemibagrus nemurus fingerling with Resirculation System - Lisa Andriani; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe aim of this research was to determine the effect of substation of Tubifex sp. with artificial feed and growth, survival rate and feed efficiency of Hemibagrus nemurus fingerling.This research was conducted from February-March 2020 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty of Riau University. The method used was an experumental method with completely randomized design with (RAL) one fator, seven treatment and three replication. The treatments in this research was T30 (given Tubifex sp. 30 days), Pm30 (given mem pellets 30 days), Pf30 (given prima feed pelets 30 days), T10Pm20(given Tubifex sp. 10 days + mem pelets 20 days), T20Pm10 (given Tubifex sp. 20 days + mem pelets 10 days), T10Pf20(given Tubifex sp. 10 days + prima feed pelets 20 days), T20Pf10 (given Tubifex sp. 20 days + prima feed pelets 10 days). The subjects used in this research were 5 days Hemibagrus nemurus fingerling. The research conducted by Hemibagrus nemurus fingerling in an aquarium 15 liters of water with a stocking density of 2 fish/liter for 30 days with resirculaion system. Frequency of feeding that conducted was three times a days as much as 80% for given Tubifex sp., and 13% for given artificial feed of the weight biomass. The result showed that T20Pm10 (given Tubifex sp. 20 days + mem pelets 10 days) the absolute weight growth was 1,27 g, the absolute length growth was 4,40 cm, specific growth rate was 20,16%/day, feed efficiency 36,16% and survival rate 92,22%.Keywords : Hemibagrus nemurus; Tubifex sp., Artificial Feed,Survival rate.